Content analysis and optimization suggestions for China's big data on healthcare policy from the perspective of policy tools - Quansheng Wang; Guoqing Han; Lansong Huang (Digital Health)
Objective To understand the internal and external characteristics of the big data policy of healthcare in China. This paper discusses the focus and shortcomings of policy objectives and related policies. This study provides a reference for optimizing China's big data-related healthcare policies. Methods In this study, NVivo 12 was used for qualitative and quantitative analyses of the combination of the software policy. The policy documents included in the study were coded, and the statistical description method was used to analyze the relevant policy tools. Results Among the basic types of policy instruments, supply-oriented, environmental, and demand-oriented policy instruments accounted for 58.9%, 24.2%, and 16.9%, respectively. The use of specific tools for different types of policy is also very uneven. Conclusions The policy is dominated by the government; its use is insufficient; some are neglected, and the system is quite different. It is suggested to improve the precision of policy targeting, optimize the internal structure of policies, actively cultivate market players, and enhance the use of information technology.